Education for All? Measuring Pro-Poor Educational Outcomes in Developing Countries - Kenneth Harttgen; Stephan Klasen; Mark Misselhorn (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
Achieving progress in education is of fundamental importance for human development. Low levels of access to the education system and in educational outcomes in developing countries are often accompanied by high inequality between countries and within countries between population subgroups. This paper analyzes differences in improvements in the access to the education system and in educational outcomes across the welfare distribution between and within countries, and also by gender and regions for a sample of 37 developing countries using Demographic and Health Surveys (DHS). For the analysis, the toolbox of the growth incidence curves is applied to several educational indicators. We found an overall positive development in education. However, we do not identify a clear pro-poor trend in progress in education between and within countries. We do find strong differences in education between males and females and between rural and urban areas. While gender inequality tends to decrease slightly, large differences by region tend to persist over time.
Keywords: 330; Pro-Poor Growth; Education; Growth Incidence Curve